PERLAKUAN AKUNTANSI ZAKAT PADA BADAN AMIL ZAKAT (STUDI KASUS PADA BADAN AMIL ZAKAT KABUPATEN SIDOARJO) - SEPTA SUMARNO, MIFTAHULLAIL Septa (Jurnal Akuntansi AKUNESA, 2014)
The receipt of funds zakat, infaq and alms (ZIS) managed by BAZNAS very great that requires accountability and utilization of zakat, infaq and alms. In accordance with Law No 23 in 2011 about management of zakat in chapter II article 7 points to four governing a task or function of of amil and zakat in the reporting and accountability the implementation of the management of zakat. To implement reporting and accountability, the amil of zakat need not only set accounting standards on reporting, but also set about recognition , the measurement of , presentation and disclosure that is concerned about management of zakat. Based on the analysis that has been done, obtained that treatment presentation of zakat which related to accounting and reporting its not based on PSAK 109. BAZNAS Kabupaten Sidoarjo only made report the receipt and the distribution of zakat, infaq and alms. While for recognition, measurement and disclosure are in accordance with PSAK 109. Keywords: Accounting of Zakat, PSAK 109, BAZNAS Kabupaten Sidoarjo.